1977
DOI: 10.1080/0360127770020308
|View full text |Cite
|
Sign up to set email alerts
|

Children's Attitudes Toward the Elderly: Educational Implications

Abstract: The CATE (Children's Attitudes Toward the Elderly) was administered to 180 children, 20 at each level from age 3 to age 11. Results suggest that children at all age levels have limited knowledge of and contact with older people. Few children gave positive responses about growing old themselves; most did not perceive being old as positive. Attitudes of children toward the elderly suggest a mixture of positive feelings of affect and either stereotypic or negative attitudes about the physical aspects of age. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 4 publications
2
39
0
Order By: Relevance
“…As Seefeldt et al (1977) indicated, educating children to develop positive attitudes toward the elders is a life long process. We need to facilitate this process to continue toward the positive direction through nursing education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Seefeldt et al (1977) indicated, educating children to develop positive attitudes toward the elders is a life long process. We need to facilitate this process to continue toward the positive direction through nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes are thought to be learned by trial and error or by teaching process of socialization (Seefeldt, et al, 1977). We need to focus on making this socialization useful in changing students attitudes toward the elderly.…”
Section: Characteristics Associated With the Attitudes Toward The Eldmentioning
confidence: 99%
“…Evaluative or affective attitude contents represent an individual's feelings and subjective evaluations of the attitude object while intentional or conative attitude contents represent the actions proposed by an individual based upon his or her beliefs and subjective evaluations towards the attitude object. These components of attitude, while not being accepted by all researchers, are the basis of attitude measures in much of the literature on attitudes of children toward the elderly (Aday et al, 1991;Seefeldt, 1987b;Dellman-Jenkins, Lambert, Fruit, & Dinero, 1986;Knox et al, 1986;Marks et al, 1985;Baggett, 1981;Jantz, Seefeldt, Galper, & Serock, 1977;Seefeldt et al, 1977a;Thomas & Yamamoto, 1975;Rosencranz & McNevin, 1969;Golde & Kogan, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…Old people were evaluated more positively on the affective dimension but more negatively on the cognitive dimension than were young people. Similarly, Seefeldt et al , (1977a) and Jantz et al , (1977) found among children three to eleven years of age, positive affective feelings but negative physical attributes towards the elderly and overall negative attitudes toward older adults. These results are supported by Serock et al , (1977) where children attributed more negative physical qualities and more positive affective qualities to the elderly.…”
Section: Negative Attitudes Toward the Elderly 16mentioning
confidence: 99%
See 1 more Smart Citation